A bivariate process-based mean residual lifetime model for maintenance and inspection planning. (January 2022) - Ahmadi, Reza
Highlights: A generic mean residual lifetime model is explored. The model outperforms the ordinary MRL and existing age and state-dependent MRLs. The characterization problem is addressed for the explored model. An age-state-dependent inspection and threshold-type replacement policy is given. Abstract: In this paper, we present a new performance metric for the reliability analysis of a deteriorating system composed of n parallel subsystems. The explored model outperforms the ordinary mean residual lifetime (MRL) and other state-dependent MRL models in the actual circumstance that it incorporates not only the age factor, but also two basic processes: the number of failed subsystems and the operating environment. Using the new model as a decision variable and the average cost rate as a measure of policy, we further examine a maintenance optimization problem for the joint determination of an optimal inspection interval and a replacement rule. The proposed model and, in particular, the behavior of the optimal solutions as the model parameters vary are illustrated through numerical examples.